Anticoagulation and monitoring in pediatric extracorporeal membrane oxygenation - Jamie Weller (Egyptian Journal of Critical Care Medicine, 2018)
Anticoagulation during extracorporeal membrane oxygenation (ECMO) is necessary to prevent catastrophic circuit clotting, but hemorrhagic and thrombotic complications continue to contribute to significant morbidity and mortality for patients. Anticoagulation for pediatric patients on ECMO can be particularly challenging due to their immature hemostasis and the inflammatory response that ensues from the extracorporeal circuit. This review article gives an overview of the various anticoagulants utilized during ECMO and the common tests used to monitor and titrate anticoagulation to minimize complications. Keywords: Anticoagulation, Unfractionated heparin, Bivalirudin, Extracorporeal membrane oxygenation